2019
DOI: 10.1038/s41598-019-50192-2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neurocognitive and psychomotor performance in patients with inflammatory bowel disease

Abstract: Limited evidence exists regarding cognitive and psychomotor function in patients with inflammatory bowel disease (IBD). Therefore, we aimed to compare the neurocognitive and psychomotor function of 60 IBD patients with 60 age/sex-matched controls. Computer-based instrument Complex Reactinometer Drenovac (CRD) was used for assessment of cognitive domains: convergent thinking (simple mathematical tasks; CRD-11), perceptive abilities (light signal position discrimination; CRD-311) and sophisticated operative thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Aging accelerates the incidence of neurodegenerative disorders and gut dysbiosis, which causes inflammatory bowel disease (IBD) [33,34]. Patients with IBD display cognitive impairments and psychomotor performance, particularly during the active stage of the disease [35,36]. The treatment of patients with IBD by an anti-inflammatory drug alleviates the brain function involved in visceral sensitivity and cognitive-affective biases [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Aging accelerates the incidence of neurodegenerative disorders and gut dysbiosis, which causes inflammatory bowel disease (IBD) [33,34]. Patients with IBD display cognitive impairments and psychomotor performance, particularly during the active stage of the disease [35,36]. The treatment of patients with IBD by an anti-inflammatory drug alleviates the brain function involved in visceral sensitivity and cognitive-affective biases [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, additional studies in which both structural neuroimaging and cognitive testing are performed in the same cohort of patients are needed to verify this hypothesis. These observations also need to be integrated with the recent reports of impaired neurocognitive and psychomotor function across areas of convergent thinking, perceptive abilities and sophisticated operative thinking ( Tadin Hadjina et al., 2019 ) as well as cognitive inflexibility ( Petruo et al., 2017 ). Emotional processing biases have also been reported to contribute to co-morbid depression among people with IBD ( Wilkinson et al., 2019 ) while anxiety symptoms were associated with slower processing speed, lower verbal learning, and lower working memory performance ( Whitehouse et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this investigation a limited number of cognitive assessments had been reported in IBD, with the most consistent finding being reduced verbal IQ performance ( Berrill et al., 2013 ; Dancey et al., 2009 ). More recently, impaired neurocognitive and psychomotor function across areas of convergent thinking, perceptive abilities, sophisticated operative thinking, processing speed, verbal learning, and delayed recall memory ( Tadin Hadjina et al., 2019 ; Whitehouse et al., 2019 ) as well as cognitive inflexibility have been reported ( Petruo et al., 2017 ). Attention and memory impairments have also been reported in pediatric patients with IBD ( Piasecki et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further support for alterations in brain function in UC comes from several studies which have demonstrated a decline in cognitive function in IBD patients [ 10 12 ] and patients with other chronic inflammatory diseases [ 13 15 ]. A recent epidemiological study demonstrated a significantly increased risk for developing Alzheimer’s disease (AD) in patients with longstanding UC [ 11 ].…”
Section: Introductionmentioning
confidence: 99%